An innovative approach for reducing the water and alkali consumption in the lactic acid fermentation via the reuse of pretreated liquid. (May 2022) - Ma, Xiaoyu; Gao, Ming; Liu, Shuo; Li, Yuan; Sun, Xiaohong; Wang, Qunhui
Graphical abstract: Highlights: Pretreated liquid reuse led to a 23.0% increase for lactic acid concentration. The water and alkali usage decreased by 84.6% and 52.0%, respectively. The optical purity of the L-lactic acid reached 99.5% by reusing pretreated liquid. Pretreated liquid detoxification can reduce the phenols concentration by 70.3%. Nearly zero discharge of wastewater was achieved in the proposed approach. Abstract: This study focuses on enhancing lactic acid (LA) production and declining water and alkali consumption by reusing the pretreated liquid (PL) of spent mushroom substance (SMS) in the co-fermentation of food waste (FW) and SMS. First, the compositions of PL are identified, and the effects of the PL inhibitors on enzymatic hydrolysis and fermentation are explored. The PL phenol concentrations exceeded 2 g/L, which affected LA fermentation. Therefore, PL phenols were removed by adjusting the pH value, and the detoxified PL (DPL) phenol concentrations were 70.3% lower than those of PL. Different PL:DPL ratios were established to reuse in the fermentation process, and the LA concentration in the 50% PL + 50% DPL group was the highest (56.7 g/L). Then, pretreated SMS was not water-washed, and a neutralizer was prepared with the PL, LA production remained unchanged. Water and NaOH consumption decreased by 84.6% and 52.0%, respectively, and no wastewater was produced.